(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The development of autonomous energy supply systems is among the priority ways of scientific and technological growth in the Russian Federation. The autonomous energy supply module providing the consumer with heat, electric power, hot and cold water can contain the different variants of the electric power subsystem. This paper considers three different variants of building the electric power subsystem for the rotary expansion engine used as a driving machine whereas the permanent magnet synchronous machine is used as a generator. Also the designed structure of 30 kW electric power supply subsystem is regarded.